style and time - Lidin, Konstantin (project baikal, 2021)
Every time creates its style, and the style reflects its time and mostly forms the image kept in the succession throughout the following ages. In continuation of the series of articles by Petr Kapustin devoted to the history and philosophy of separate architectural elements, we are publishing the material on pilasters and their transformations in the context of different styles and times.
Keywords: style; time